How AI Tools are Accepted and Utilized in Academia: A Mixed Methods Study - Fabia, Jose Noel; Napoles, Vanessa; Goh, Joselito Eduard; Borbon, Jr., Mateo (Journal of Social and Scientific Education, 2025)
This mixed methods study investigates the factors influencing the acceptance and utilization of Artificial Intelligence (AI) tools among students and associates in a Philippine higher education institution, using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The study reveals that both groups exhibit high familiarity with AI and utilize it for various academic tasks, with performance expectancy and facilitating conditions identified as the primary drivers of acceptance. The study employed a cross-sectional design with an embedded parallel mixed-methods approach. An online survey questionnaire was used to investigate the usage and acceptance of AI tools among students and associates. The findings underscore the importance of comprehensive training, transparent AI governance, and ethical guidelines to foster responsible AI integration in academia. The study also discusses the ethical considerations surrounding AI's use in education, emphasizing the need for responsible implementation to maximize its benefits while minimizing potential risks.